143k views
1 vote
What is 9 1/6 - 3 2/9​

User Panagiotis
by
5.4k points

2 Answers

1 vote
so 9 1/6 - 3 2/9

You want to reduce 9 and 6 ( 9 1/6)

It now becomes 3 1/2 .

then reduce the 3 and the 9 (3 2/9)

Now it becomes 2/3.


3 * (1)/(2)

Calculate or Multiply 3 •1 which is obviously 3
and now the equation becomes

3/2 - 2/3= 5/6
but how?
you have to find the numerators.

3x3 =9
2x3=6

2x2=4
3x2=6

Subtract all the numbers

9/6 - 4/6= 5/6
hope this helps!
User Marcal
by
5.7k points
4 votes

Answer:

5 17/18

Explanation:

9 1/6 - 3 2/9

9 1/6*3/3 - 3 2/9*2/2

9 3/18 - 3 4/18

=9-3=6 but since 3-4=-1 you result with 1/18 less than 6 which is 5 17/18...hope you understand.

User Faliorn
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.